Comparison between the Interferon γ Release Assay—QuantiFERON Gold Plus (QFT-Plus)—and Tuberculin Skin Test (TST) in the Detection of Tuberculosis Infection in Immunocompromised Children - Primaturia, Cory; Reniarti, Lelani; Nataprawira, Heda M. N. (Pulmonary Medicine, 2020)
Background. Immunocompromised patients are at a higher risk of having latent tuberculosis infection (LTBI). QuantiFERON-TB Gold Plus (QFT-Plus) has been proven to perform effectively in LTBI detection among immunocompromised adults and can overcome the limitations of the tuberculin skin test (TST). However, the role of QFT-Plus in detecting LTBI in immunocompromised paediatric patients has not been well established. Therefore, the aim of this study was to assess the test agreement between QFT-Plus and the TST in LTBI detection among immunocompromised children. Method. In this cross-sectional study, we enrolled immunocompromised paediatric patients, aged between 5 and 18 years, who were treated with corticosteroids and/or chemotherapy from June to November 2019. We categorized them into three groups based on the following diseases: hematologic malignancies and nephrological and immunological diseases. We recorded the patient characteristics and QFT-Plus and TST results, in which the positive result of the TST was induration≥5 mm. Within the same group, comparisons between the two tests were performed using the McNemar test, and results were statistically significant for p values of <0.05. The kappa index was used to assess the agreement between the two test results. Results. Among 71 patients (median age: 11.8 years) who underwent TST and QFT-Plus testing, 52% were females, and 69% had a normal nutritional status. Chemotherapy was the most common treatment modality for hematologic malignancy compared to other immunosuppressive treatments. The total number of patients with positive QFT-Plus and TST results was 11/71 (15.5%) and 4/71 (5.6%), respectively, among whom 3/11 patients had positive results in both tests, and one patient with positive TST results exhibited a discrepancy, as this was not followed by positive QFT-Plus results. QFT-Plus generated more positive results than the TST in immunocompromised children (McNemar, p=0.039 (p<0.05)). The diagnostic agreement between the tests was fair (K=0.345, 95% CI: 0.05–0.745). Conclusion. QFT-Plus detected LTBI more effectively than the TST in immunocompromised children.